Test-Taking Strategy Use and Reading Test Scores: Dire Dawa University Students in Focus - Mamo, Mesfin; Regassa, Taye (Journal of Linguistics, Literature, and Language Teaching (JLLLT), 2024)
This research delves into the utilization of metacognitive and cognitive strategies by Ethiopian test-takers during reading assessments. Specifically, the primary objective of this quantitative study is to explore the relationship between the employment of test-taking strategies and the achievement of reading comprehension scores. Furthermore, the study investigates the specific test-taking strategies that university students employ to succeed in reading comprehension tests. Data were collected via a questionnaire and the TOEFL test from 40 senior students at a university in Ethiopia. The findings indicate that the test takers predominantly employ metacognitive strategies, achieving a higher mean score of 3.12 compared to cognitive strategies, with a mean score of 2.73, in the context of reading comprehension tests. Additionally, the study uncovers a positive correlation between the use of test-taking strategies and reading comprehension scores.